Implementación de las normas internacionales de información financiera (niif) en la empresa flores de decoración “Decoflor” S.A., ubicada en la provincia de Cotopaxi, cantón Latacunga, sector Lasso, al periodo 2013 - Heredia Villalva, Denisse Yaninka (2015)
The research provided to the company of opportune manner and reliable the way to obtain, evidence and present its accounting-financial information to national and international level, fulfilling regulation that present the organism or regulator entity, in order to standardize the information obtained. The ISFR (International Standards of Financial Reporting) involved a fundamental change culture of the company and the traditional vision of the accounting, they were designed to be applied in the financial statements, whose objective was reflect the economic essence of the business operations and present an original image of the company financial situation. The present research in the accounting- financial area required standardize the information for its interpretation, trying to make works team, evaluate the actual situation and possible impacts in each procedure, standard or accounting-financial politics of the company, whose management and utility was low EAS (Ecuadorian Accounting Standard)….